2022
DOI: 10.1055/s-0042-1751002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan and Acrylic Acid Addition to Acrylic Resin on Porosity and Streptococcus mutans Growth in Denture Base

Abstract: Objective This work aimed to determine the effect of adding chitosan and acrylic acid to acrylic resin denture base on the porosity of the material and the growth of Streptococcus mutans. Materials and Methods This study is an experimental laboratory research. Samples were divided into the following three groups (n=10): group 1 was the control group, group 2 was the acrylic resin mixture with 1% chitosan and acrylate acid, and group 3 was the acrylic resin mixture with 2% chitosan and acrylate acid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Results of the present study showed that the antimicrobial effect increased by increasing the percentage of the added chitosan nanoparticles to the heat cured acrylic resin, these results were in accordance with (30,31) . But increasing the percentage of chitosan can affect the mechanical properties of the heat cured acrylic adversely, for this reason its recommended to add chitosan nano particles with a percentage less than 1% (32) .…”
Section: Methods For Testing Propertiessupporting
confidence: 85%
“…Results of the present study showed that the antimicrobial effect increased by increasing the percentage of the added chitosan nanoparticles to the heat cured acrylic resin, these results were in accordance with (30,31) . But increasing the percentage of chitosan can affect the mechanical properties of the heat cured acrylic adversely, for this reason its recommended to add chitosan nano particles with a percentage less than 1% (32) .…”
Section: Methods For Testing Propertiessupporting
confidence: 85%
“…This phenomenon occurred because even after the polymerization of acrylic resin without a mixture, some monomers did not bind to the polymer and instead formed pores. Meanwhile, acrylic acid can function as a coupling agent to form bonds between acrylic resin and chitosan; hence, the monomers contained in the acrylic resin can be bonded during polymerization [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this polymerization can reduce the formation of pores. The decrease in the amount of residual monomer can reduce the formation of space known as porosity [29]. A large pore size will allow the easy absorption of liquid, which in turn will reduce the density and other mechanical properties of the acrylic resin [31,32].…”
Section: Introductionmentioning
confidence: 99%